Effect of moderate-intensity aerobic exercise on bladder TGF-β1 and type I collagen expressions in diabetic rat model - Fatahajjad, Haykal H.; Soebadi, Mohammad A.; Putra, Rheza M.; Sulastri, Nur; Rahaju, Anny S. (Narra J, 2024)
Transforming growth factor-beta 1 (TGF-β1) and type I collagen play crucial roles in the pathogenesis of diabetic bladder disease (DBD). Moderate-intensity aerobic exercise increases antioxidant activity to help manage DBD. The aim of this study was to evaluate the effect of moderate-intensity aerobic exercise on the expression of TGF-β1 and type I collagen in the detrusor and lamina propria of the bladder in a type 2 diabetes mellitus (T2DM) rat model. A true experimental design with a post-test-only control group design was conducted with white rats (Rattus norvegicus), divided into three groups: a T2DM model group sacrificed after T2DM induction and diagnosed with T2D from a fasting blood glucose (FBC) test (Group C), a T2DM model group that did not receive exercise (Group NE), and a T2DM model group that received moderate-intensity aerobic exercise (Group E). Moderate-intensity aerobic exercise was conducted over six weeks, with a frequency of five days per week for 60 minutes per session. The findings revealed a significant reduction in TGF-β1 expression in the lamina propria in Group E compared to Group C (p=0.004) Additionally, both Group E (p=0.002) and Group NE (p=0.028) showed a significant reduction in type I collagen expression in the lamina propria compared to Group C. These findings provide a basis for further investigation regarding the mechanism of non-pharmacologic DBD management by employing moderate-intensity exercise.